Myelopreservation with Trilaciclib in recurrent advanced ovarian cancer: a case report - Tan, Huaming; Han, Xiuchen; Li, Chao; Liu, Wenli; Li, Kanghong; Sheng, Xiugui; Qi, Shuying (Frontiers in Oncology, 2024)
Ovarian cancer is a prevalent malignant tumor of the female reproductive system, often remaining concealed until it reaches an advanced stage. The standard treatment protocol includes cytoreductive surgery for ovarian cancer plus postoperative consolidation chemotherapy and maintenance therapy, although it carries a high recurrence rate. During the treatment period, chemotherapy can lead to bone marrow suppression, a condition known as Chemotherapy-Induced Myelosuppression (CIM). This suppression may necessitate dose reduction or chemotherapy treatment cycle delay. In severe cases, CIM can result in infection, fever, and potential harm to the patient’s life. Here, we report a case of a female patient with ovarian malignant tumor of biochemical recurrence who treated with chemotherapy combined with Trilaciclib, following previous perioperative chemotherapy with occurrence of severe CIM. It involves an intravenous injection of Trilaciclib before chemotherapy, which significantly abates the side effects of chemotherapy, reduces the occurrence of severe CIM, improves the patients’ quality of life, and decreases the economic burden of hospitalization. We hope that this retrospective analysis of the case may serve as a reference in preventing and treating severe CIM during chemotherapy in some patients with malignant tumors, ultimately benefiting more patients with tumors.